Declining trust in growing China: A dilemma between growth and socio-economic damage - Shuanping Dai; Wolfram Elsner (University of Duisburg-Essen, Institute of East Asian Studies (IN-EAST), 2015)
Declining general trust has become a serious social issue in China in recent years. This paper attempts to understand and analyze this social phenomenon from a social interaction perspective. Based on a repeated prisoners dilemma game on networks, it finds that the evolution of general trust is dependent on changes of the social interaction structure, and the increases of both social and spatial distance may explain a decrease of the levels of cooperation and general trust. In addition, we find that the traditional Chinese family and clan networks culture has an ambiguous effect on general trust, and simple reactive social "homing behavior" might be critical for Chinas future economic development. In order to recover the general trust level, a major strategic option for China, and for fast growing countries in economic transition in general, is to (re-)develop appropriate network structures and properties, as our model indicates.
Keywords: B52; C72; D01; D02; D30; E24; O17; O43; O53; P21; Z10; 330; economic transition; growth and development; migration; trust; games on networks; China